2007
DOI: 10.1007/s10157-007-0476-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremic seizure associated with acute respiratory infection

Abstract: A 66-year-old woman was admitted to our hospital because of vomiting and appetite loss. For the 2 days prior to admission, she had a cold, which had developed into acute viral bronchitis on admission. Because laboratory data on admission showed hyponatremia, intravenous infusion of Ringer's lactate solution was started. However, generalized seizures appeared, and she developed a coma on the day of admission. Her plasma antidiuretic hormone (ADH) level was high in the context of a low serum osmolality on the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Miscellaneous cases of water intoxication identified in this review included anorexia nervosa, 112 a self-remedy for chronic hiccups, 62 93 123 replacing fluids during acute gastroenteritis 83 109 or respiratory tract infection 145 ; providing a urine sample for drug testing. 10 128 132 167 In the latter case, paruresis (difficulty urinating in public; present in up to 25% of the general population) may lead to emotion stress and antidiuretic hormone release and lower the threshold for water intoxication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miscellaneous cases of water intoxication identified in this review included anorexia nervosa, 112 a self-remedy for chronic hiccups, 62 93 123 replacing fluids during acute gastroenteritis 83 109 or respiratory tract infection 145 ; providing a urine sample for drug testing. 10 128 132 167 In the latter case, paruresis (difficulty urinating in public; present in up to 25% of the general population) may lead to emotion stress and antidiuretic hormone release and lower the threshold for water intoxication.…”
Section: Discussionmentioning
confidence: 99%
“…55 159 Although iatrogenic polydipsia is probably very rare, these cases highlight the need for healthcare workers to be more specific when providing instructions about the volume and rate of water intake (such as, 'drinking three glasses of water (750 mL) spread over a period of 2 hours') 108 117 140 172 and to adhere to evidence-based guidelines. 180 Miscellaneous cases of water intoxication identified in this review included anorexia nervosa, 112 a self-remedy for chronic hiccups, 62 93 123 replacing fluids during acute gastroenteritis 83 109 or respiratory tract infection 145 ; providing a urine sample for drug testing. 10 128 132 167 In the latter case, paruresis (difficulty urinating in public; present in up to 25% of the general population) may lead to emotion stress and antidiuretic hormone release and lower the threshold for water intoxication.…”
Section: Discussionmentioning
confidence: 99%
“…Lee and Ho 11 reported hyponatremia in a patient with pulmonary tuberculosis, which may be caused by the ectopic secretion of antidiuretic hormone. Iwazu et al 12 reported a case of hyponatremic seizure associated with acute viral bronchitis. In our patient, a chest CT scan also indicated bilateral lung infection, which may also precipitate the occurrence of hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, risk factors for developing hyponatremia include older age, female sex, use of thiazide diuretics, previous history of hyponatremia, low body weight (<60 kg), and psychosis 6 . Moreover, chronic or acute lung infection may also increase the risk of developing hyponatremia 11,12 . Lee and Ho 11 reported hyponatremia in a patient with pulmonary tuberculosis, which may be caused by the ectopic secretion of antidiuretic hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports on severe hyponatremia caused by excessive water intake in the elderly people with high plasma ADH levels have been reported in Japan and Hungary. 13,14 Other researchers, namely Chute JP at al. 15 has done a metabolic study on 24 patients.…”
Section: Selection Of Subjects and Laboratory Testsmentioning
confidence: 99%